The Construction of Therapeutic Space in Emotional Wellness Apps: An Interaction Design Study Based on the Theory of the Production of Space - Zhang, Qi; Xu, Buyu; Zhu, Lin; Wu, Yichen (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
INTRODUCTION: In response to the global shortage of mental health resources, the design paradigm of emotional wellness apps is shifting from “functional tools” to “immersive spaces.” However, existing research lacks a systematic framework to analyze the therapeutic mechanisms of “spatiality” in such applications. OBJECTIVES: Based on Henri Lefebvre’s theory of the production of space, this study employs an exploratory sequential mixed-methods approach to construct and preliminarily validate a model of digital therapeutic space in emotional wellness apps for empirical analysis. METHODS: The study first conducted semi-structured interviews with 24 intensive users of three representative apps, “Chao Xi,” “MoFlow,” and “Xin Guang.” Grounded theory was used for three-level coding to extract core categories and construct a theoretical model. Subsequently, based on qualitative coding results, the Spatial Narrative Experience Assessment Scale was developed and administered to 286 users. Descriptive statistics, correlation analysis, multiple linear regression, and Bootstrap methods were used to test model pathways, controlling for common method bias. RESULTS: The results show: (1) The therapeutic space of emotional wellness apps is a systematic model comprising three main categories (physical space, social space, and spiritual space) and nine subcategories. (2) Qualitative analysis revealed a carrier-rule-output spatial logic. (3) After controlling for usage duration and mental health baseline, physical space (β = 0.29, p < 0.001) and social space (β = 0.38, p < 0.001) significantly positively influenced spiritual space experience. Bootstrap tests indicated no significant difference in their effects (95% CI [-0.03, 0.21]), supporting a “Dual Engine Drive” mechanism. Common method bias was acceptable (first-factor explanation rate: 32.7%). CONCLUSION: This study validates the operationalization of the theory of the production of space in interaction design research, providing a systematic theoretical model and empirical basis for the construction and evaluation of “digital therapeutic space.” The derived “carrier-rule-output” framework offers actionable insights for the design of emotionally resonant digital environments.